IMPLEMENTASI SUPERVISI KLINIS KEPALA SEKOLAH DALAM PEMBELAJARAN DI SD NEGERI COA KAIMANA PAPUA BARAT - Ridwan Fadli; Yulius Mataputun; Indah Slamet Budiarti (Vidya Karya, 2021)
This study aimed to analyze the planning, implementation, and feedback stages of clinical supervision of principals in learning at SD Negeri Coa Kaimana. This study used a descriptive method with a qualitative analysis approach. The subject of the research were the principal, teachers, and school staff, about 16 people. This study indicated that the principal of SD Negeri Coa Kaimana had implemented a clinical supervision program in learning with three stages. Before implementing the clinical supervision program, the principal by involving the vice principal, the curriculum section, senior teachers and classroom teachers to plan what they wanted to be supervised according to the needs and needs of the teacher, such as compiling a schedule of supervision, goals, objectives, steps, and time. The principal supervised the implementation of clinical supervision such as coming to the classroom to see classroom learning activities, preparing learning equipment such as lesson plans, syllabus, Prota, Prosem, assessment, teaching aids, handbooks, and learning media. Based on research, it was known that the principal's clinical supervision research in learning was clinical supervision feedback such as calling the supervised teacher to be fostered and followed up. However, some were a little difficult to foster. The teachers also increasingly understood their duties as educators.Keywords: Clinical Supervision; Learning; PrincipalPenelitian ini bertujuan untuk menganalisis implementasi tahap perencanaan, pelaksanaan, dan umpan balik supervisi klinis kepala sekolah dalam pembelajaran di SD Negeri Coa Kaimana. Penelitian ini menggunakan metode deskriptif dengan pendekatan analisis kualitatif. Subjek penelitian supervisi ini adalah kepala sekolah, guru, dan tenaga kependidikan sebanyak 16 orang. Hasil penelitian ini menunjukkan bahwa kepala SD Negeri Coa Kaimana telah melaksanakan program supervisi klinis dalam pembelajaran dengan tiga tahapan. Sebelum melaksanakan program supervisi klinis, kepala sekolah dengan melibatkan wakil kepala sekolah, bagian kurikulum, guru senior, dan guru kelas untuk merencanakan parameter yang hendak disupervisi berdasarkan kebutuhan guru seperti menyusun jadwal dan tujuan supervisi. Kepala sekolah melakukan supervisi pelaksanaan supervisi klinis, seperti visitasi ruang kelas untuk melihat kegiatan pembelajaran, aktualisasi RPP, silabus, Prota, Prosem, penilaian, alat alat peraga, buku pegangan, dan media pembelajaran. Berdasarkan hasil penelitian diketahui bahwa supervis klinis kepala sekolah dalam pembelajaran adalah umpan balik supervisi klinis seperti memanggil guru yang disupervisi untuk dibina dan ditindaklanjuti. Kendati demikian, ada sebagian guru yang sedikit sulit untuk dibina. Mereka juga perlahan memahami tugas sebagai pendidik.Kata Kunci: Supervisi Klinis; Pembelajaran; Kepala Sekolah